The Role of Job Satisfaction in Mediating Employee Engagement on Employee Performance - Syaiful Arifin, (International Journal of Research in Social Science and Humanities (IJRSS) ISSN:2582-6220, DOI: 10.47505/IJRSS, 2024)
This research aims to analyze the effect of employee engagement on job satisfaction, analyze employee engagement on employee performance, analyze job satisfaction on employee performance and analyze job satisfaction in mediating employee engagement on employee performance. The sample in this research was 120 employees. The data analysis technique uses SmartPLS. The results of the analysis show that employee engagement influences job satisfaction. Employee engagement influences employee performance. Job satisfaction influences employee performance. Job satisfaction mediates the effect of employee engagement on employee performance.